Draught animal power network [2] - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
a directory of draught animal power activities in 45 African countries, including detailed information on the main institutions involved, written by P Starkey, an English specialist in this field, has been published by GTZ, the West German Agency for Tech